2021
DOI: 10.1021/jacs.1c03661
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Adaptable Liquid Crystal Networks Enabled by Reversible Ring-Opening Cascades of Cyclic Disulfides

Abstract: The development of covalent adaptable liquid crystal networks (LCNs) enabled by introducing dynamic covalent bonds has endowed liquid crystal actuators with self-healing properties and reversible shape programmability, broadening their applications in diverse soft robotic devices. However, the finite molecular design strategy limits the recyclability and the architectural diversity of these materials. Here, a strategy is first reported for fabricating photoresponsive polydisulfide-based covalent adaptable LCNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 41 publications
0
112
0
Order By: Relevance
“…It is a natural and feasible strategy to design and fabricate 2W‐SMPAs starting from traditional two‐way shape‐memory polymers. As an intriguing category of two‐way shape‐memory materials, liquid crystal elastomers (LCEs), [ 15 , 16 , 17 , 18 ] possessing both anisotropic properties of liquid crystals (LCs) and the rubber elasticity, could perform a large and reversible macroscopic shape deformation between two different permanent shapes due to the change in the molecular order of the mesogens during the LC‐to‐isotropic phase transition process induced by external stimuli, and have exhibited prosperous applications in mechanical actuators, [ 19 , 20 , 21 , 22 ] artificial organs, [ 23 , 24 ] smart surfaces, [ 25 , 26 ] and more. Such excellent properties suggested the potential of LCEs to be suitable materials for realizing novel 2W‐SMPAs.…”
Section: Introductionmentioning
confidence: 99%
“…It is a natural and feasible strategy to design and fabricate 2W‐SMPAs starting from traditional two‐way shape‐memory polymers. As an intriguing category of two‐way shape‐memory materials, liquid crystal elastomers (LCEs), [ 15 , 16 , 17 , 18 ] possessing both anisotropic properties of liquid crystals (LCs) and the rubber elasticity, could perform a large and reversible macroscopic shape deformation between two different permanent shapes due to the change in the molecular order of the mesogens during the LC‐to‐isotropic phase transition process induced by external stimuli, and have exhibited prosperous applications in mechanical actuators, [ 19 , 20 , 21 , 22 ] artificial organs, [ 23 , 24 ] smart surfaces, [ 25 , 26 ] and more. Such excellent properties suggested the potential of LCEs to be suitable materials for realizing novel 2W‐SMPAs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other dynamic elastomers, the basic properties imparted by the dynamic bonds to LCEs are the abilities of self-healing, reprocessing, recycling, or welding, which are demonstrated by many dynamic LCE systems based on transesterification, [149,242,253,254] disulfide, [250,251,[255][256][257] DA, [247] diselenide, [258] siloxane exchange, [259] and hydrogen bonds. [260,261] Ji et al have synthesized a photo-healable LCE vitrimer through the reaction between diglycidyl ether of 4,4'dihydroxybiphenol and sebacic acid.…”
Section: Self-healing Recycle Welding Performances Of Dynamic Liquid ...mentioning
confidence: 99%
“…Recently, Yang et al reported a novel strategy to prepare disulfide bond-containing LCEs via ring-opening polymerization of cyclic dithiolane groups. [256] The functionalized LC monomers with dithiolane moieties could undergo ring-opening reaction to form entire disulfide bonding backbones with the presence of the initiator of 1,6-hexanedithiol and the catalyst of The remolding process and corresponding stress-strain curves of the original and healed LCEs. c) Schematic illustration of the polymerization and depolymerization mechanism.…”
Section: Self-healing Recycle Welding Performances Of Dynamic Liquid ...mentioning
confidence: 99%
“…While LCE actuators based on dynamic covalent networks are capable of welding, recycling, and reprogramming, materials that are melt‐processable with programmable molecular orientation render new possibilities to enable conventional processing methods using the polymer melt. Only very recently, the dynamic thermal rearrangement of a covalent adaptable network was reported enabling depolymerization and repolymerization, allowing for processing the material in the viscous melt [28] …”
Section: Introductionmentioning
confidence: 99%
“…Only very recently,t he dynamic thermal rearrangement of acovalent adaptable network was reported enabling depolymerization and repolymerization, allowing for processing the material in the viscous melt. [28] An alternative strategy to circumvent permanently crosslinked networks is by introducing supramolecular interactions as dynamic physical cross-links.A mong the potential supramolecular interactions,hydrogen bonds have emerged as one of the most attractive motives,a nd hydrogen-bonded liquid crystal (LC) polymers capable of reversible actuation have become an emerging research area. [29][30][31][32] However,s upramolecular cross-linked LCE actuators have generally been prepared by multistep synthesis,a nd reprogramming arbitrary initial shapes has not been reported (Table S1).…”
Section: Introductionmentioning
confidence: 99%